"A tongue in every star": Anna Letitia Barbauld's Poetics of Influence. Issue 2 (October 2016) - Chema, Alexis
Abstract : This essay examines how Barbauld develops an idiosyncratic theory of poetic influence enabled by her revaluation of fancy, a contested term I define as a figure for rhetorical excesses that confuse art and life. While her attraction to fancy begins as a matter of taste, fancy accrues ethical significance as she becomes skeptical that poetry can stimulate virtuous action by eliciting sympathy. Barbauld's waning faith in sentimental rhetoric leads her to formulate an inventive model of how poetry might move readers to be good: fancy's mystifying extravagances can weaken self-interested attachments, thereby producing (or approximating) the ingenuous state. The late prophetic poem Eighteen Hundred and Eleven illustrates the political radicalism of this new conception of fancy, making the utopian—and today, highly suspicious—proposition that by stimulating imaginative acquiescence, flights of fancy can influence readers against their will, and against the entrenched exceptionalism that was keeping the nation at war.